HUBUNGAN RIWAYAT PEMBERIAN ASI EKSKLUSIF TERHADAP STATUS GIZI BAYI USIA 6-12 BULAN - Putri Ladekha, Tiara Chennie; Agrina, Agrina; Hasneli, Yesi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2018)
Exclusive breastfeeding for 6 months to meet the nutritional needs of infants have an important role to the nutritional status of infants. The purpose of the study was to find out the relationship between history of exclusive breastfeeding toward infant’s nutritional status for 6 to 12 months in Payung Sekaki Health Center working area. This study was descriptive correlation with cross sectional approach. The samples in this study were mothers and infants from 6 to 12 months with 94 respondents by using cluster sampling technique. The analyzes were univariate and bivariate using the Kolmogorov-Smirnov test. The results showed that the majority of respondents were 6-month-old as much as 23.4% with normal birth weight of 96.9%. Maternal age was early adult as much as 86,2% with high school education as much as 72,3%. 69.1% of mothers did not work. The history of exclusive breastfeeding as much as 54.3% and baby's nutritional status is in normal nutrition as much as 85.1%. The results of the analysis showed that infants with a history of exclusive breastfeeding tend to have normal nutritional status of 92.2% more than malnutrition and overweight.   Based on the results of statistical tests it showed that there was no relationship between history of exclusive breastfeeding toward infant’s nutritional status for 6 to 12 months (p value = 0.868). The results of this study recommend health workers to provide health education about exclusive breastfeeding for 6 months.   Keywords: Exclusive breastfeeding, infant, nutritional status.